2007
DOI: 10.1111/j.1365-2702.2006.01719.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of a virtual reality prototype for pain relief of pediatric burn in Taiwan

Abstract: This study is significant since it demonstrates a difference in the child's response to pain based on the nature of presence and distraction. Moreover, given the evidence that a decrease in anxiety was experienced after the dressing change with virtual reality intervention, timing of using the virtual reality intervention before the child develops conditioning anxiety and anticipated pain for the procedure would be of importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 22 publications
(33 reference statements)
2
108
3
4
Order By: Relevance
“…Nurse-observed pain during and after dressing changes in the children of the VR group was significantly lower than those of the control group, whereas differences in pain before the dressing change between the two groups was not statistically significant. These results are not in concordance with those of a study about pain management in burndressing changes (Chan, Chung, Wong, Lien, & Yang, 2007). This may be due to the different VR equipment being used and differences in the patient population.…”
Section: Discussioncontrasting
confidence: 79%
“…Nurse-observed pain during and after dressing changes in the children of the VR group was significantly lower than those of the control group, whereas differences in pain before the dressing change between the two groups was not statistically significant. These results are not in concordance with those of a study about pain management in burndressing changes (Chan, Chung, Wong, Lien, & Yang, 2007). This may be due to the different VR equipment being used and differences in the patient population.…”
Section: Discussioncontrasting
confidence: 79%
“…Chan et al [24] examined the use of a VR prototype in providing relief to children with burns. The VR prototype consisted of graphic animation presented via eyeglasses, which the children controlled using a computer mouse.…”
Section: Burn Carementioning
confidence: 99%
“…Virtual reality (VR) has been shown to be an effective adjunct or alternative to opioid analgesics even in cases of high levels of pain such as burn pain and wound care [5][6][7][8][9][10][11][12][13][14][15]. These numerous studies have demonstrated that VR is an effective tool in significantly reducing pain a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 in acute pain situations.…”
Section: Introductionmentioning
confidence: 99%